1976
DOI: 10.1139/t76-043
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between cone resistance and vane shear strength in some Scandinavian soft to medium stiff clays

Abstract: Vane shear strength and cone resistance for Scandinavian soft to medium stiff clay has been compared for six different sites in Norway and Sweden.At five of the sites, three in Drammen, one in Onsøy, and one in Gøteborg, the clays have been sedimented in an entirely marin environment. At the Skå-Edeby site the conditions have been marine-brackish or brackish-marine.When compared with the standard field vane shear strength, the cone factor, Nk (in the formula: qc = Nk∙[Formula: see text]f + γ∙z), varies between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…Earlier, Lunne et al (1976) also showed a similar trend of decreasing cone factor with plastic index. Details of undrained shear strength interpretation from in situ tests could be found in the study by Bo et al (2000).…”
Section: Correlation Of Strength Parameters With In Situ Measured Parsupporting
confidence: 61%
“…Earlier, Lunne et al (1976) also showed a similar trend of decreasing cone factor with plastic index. Details of undrained shear strength interpretation from in situ tests could be found in the study by Bo et al (2000).…”
Section: Correlation Of Strength Parameters With In Situ Measured Parsupporting
confidence: 61%
“…This correlation has been successfully evaluated for numerous types of cohesive soils [23,24]. In order to check this relationship, the undrained shear strength of the soil is measured by means of shear vane, triaxial compression test or unconfined compression test.…”
Section: Cone Penetration Testmentioning
confidence: 99%
“…(2.1), given that q c , σ v , and s u are all known. However, as noted by Lunne et al (1976), there are limitations on the accuracy of s u determinations from the vane test that are related to the direction and rate of shearing (Lunne et al 1976). …”
Section: Empirical Efforts For Correlating Shear Strength To Cone Resmentioning
confidence: 99%